2021
DOI: 10.1515/lingvan-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic investigation of anticipatory vowel nasalization in a Caribbean and a non-Caribbean dialect of Spanish

Abstract: Spanish dialectology observes that dialects with a preference for velarized variants of /n/ (e.g. Caribbean dialects) include nasalized vocalic allophones in their inventory. Instrumental cross-dialectal comparisons of Spanish anticipatory nasalization, however, remain surprisingly rare. To this end, I compare the time-course of nasality in pre-nasal vowels in Argentine and Dominican Spanish, as well as across a number of linguistic variables described in the phonetic, sociolinguistic and historical literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…[ŋ]-dialects of Spanish are conceivable. Bongiovanni (2021) showed that the [ŋ]-dialect under study exhibited earlier onset of nasalization across a number of conditions. So, it is likely that Santo Domingo Spanish exhibits greater consonant weakening as well.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ŋ]-dialects of Spanish are conceivable. Bongiovanni (2021) showed that the [ŋ]-dialect under study exhibited earlier onset of nasalization across a number of conditions. So, it is likely that Santo Domingo Spanish exhibits greater consonant weakening as well.…”
Section: Methodsmentioning
confidence: 99%
“…With the previous research as a backdrop, in Bongiovanni (2021), I analyzed the time course of nasalization in Santo Domingo and Buenos Aires Spanish to test the phonetic underpinnings of anticipatory vowel nasalization in an [ŋ]-and an [n]-dialect, respectively. Findings revealed that onset of nasalization was earlier for Santo Domingo than for Buenos Aires Spanish.…”
Section: Variation In the Spanish Nasal Systemmentioning
confidence: 99%
See 3 more Smart Citations